The Chivalric Romance as a Type of Prose and Verse Narrative in Medieval English Literature - Narbayevna, Arazdurdiyeva Annasoltan (Miasto Przyszłości, 2023)
The purpose of this research is to get involved the information about theme of the chivalric romance as a type of prose and verse narrative in medieval english literature. Chivalric romance is a literary genre popular in the later medieval period and told in prose or verse. The medieval period was term retroactively by those living in the Renaissance, so was argued to be roughly the 5th century up until the 15th. Chivalric romance was popular between the 11th and 14th centuries. When we talk of chivalric romance, we do not mean romantic love stories as we normally associate with romance today. Instead, chivalric romance really means adventure stories, a bit like medieval action movies. It's all about knights going on fantastic quests, facing great dangers, winning hearts and generally acting like heroes.